2020
DOI: 10.1111/itor.12841
|View full text |Cite
|
Sign up to set email alerts
|

Optimal channel strategies in a supply chain under green manufacturer financial distress with advance payment discount

Abstract: Green manufacturers are always faced with capital constraints in reality, while the previous literature has shown that internal financing is more effective than external financing. Given manufacturers' financial constraints, this paper studies and compares the optimal green decisions and profits under single-channel or dual-channel strategies with and without green investment. Therefore, the main contribution of the paper is determining the optimal channel strategy of supply chains under advance payment financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Yang et al [5] considered a two-level GSC composed of a manufacturer and retailers with capital constraints and competition, designed revenuesharing contracts from the SC's internal and external financing channels to coordinate the profit distribution GSC. Zhang [51] compared the optimal green decisions with and without green investments under manufacturers' capital constraints. Moreover, Fang and Xu [52] compared green credit financing and hybrid financing modes and concluded that manufacturers with capital constraints were also willing to make green investments.…”
Section: Gsc Financing With Capital Constraintmentioning
confidence: 99%
“…Yang et al [5] considered a two-level GSC composed of a manufacturer and retailers with capital constraints and competition, designed revenuesharing contracts from the SC's internal and external financing channels to coordinate the profit distribution GSC. Zhang [51] compared the optimal green decisions with and without green investments under manufacturers' capital constraints. Moreover, Fang and Xu [52] compared green credit financing and hybrid financing modes and concluded that manufacturers with capital constraints were also willing to make green investments.…”
Section: Gsc Financing With Capital Constraintmentioning
confidence: 99%
“…It is easy to obtain μ > (1/2) from inequality (31). In equation ( 28), because θ ∈ [0, 1], μ > (1/2), it is to get the result (zt * /zθ) < 0 in equation ( 28), thus proving the conclusion.…”
Section: Proofmentioning
confidence: 64%
“…Wang et al study the competitive and sustainable supply chain network design problem by considering the chain-to-chain competition between two supply chains [30]. Zhang et al compare the optimal green decisions and profits under single-channel or dual-channel strategies with and without green investment [31]. Wang et al study the decisions and coordination of green e-commerce supply chain under green manufactures' fairness concerns considering the product green degree and the e-commerce platform's service [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Channel choice based on online retailing involves two types. First, some scholars focus on channel introduction, for example, the introduction of online retailing channel in addition to the offline channel (e.g., Liu and Zhang, 2006; Arya et al., 2007; Bernstein et al., 2008; Yoo and Lee, 2011; Li et al., 2015; Chen et al., 2018; Salma and Simon, 2018; Wang et al., 2018; He et al., 2019; Cao et al., 2020; Zhang et al., 2020), the supplier offline entry when it sells products through the e‐tailer (e.g., Zhang and Zhang, 2020), and whether to introduce the agency selling format in addition to the reselling format (e.g., Yan et al., 2018a; Yan et al., 2019; Chen et al., 2020). Second, some studies compare the direct channel with the agency selling format or (and) the reselling format (e.g., Ow and Wood, 2011; Yan et al., 2018b; Shen et al., 2019; Pu et al., 2020; Zhang et al., 2021a).…”
Section: Literature Reviewmentioning
confidence: 99%